1998
DOI: 10.1097/00005392-199810000-00038
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Medical Therapy on Bother Due to Symptoms, Quality of Life and Global Outcome, and Factors Predicting Response

Abstract: In men with clinical BPH finasteride and placebo are equally effective, while terazosin and combination are significantly more effective. In men with clinical BPH and large prostates the advantage of finasteride over placebo in terms of symptom reduction, impact on bother due to symptoms and quality of life is small at best, while the advantage of terazosin and combination over finasteride and placebo is highly significant. Baseline prostate volume was not a predictor of response to finasteride in the overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 19 publications
1
36
0
4
Order By: Relevance
“…In the nationwide survey, most of the PCPs also mainly prescribed α 1 -adrenoceptor antagonists whereas finasteride was used more rarely [10]. A total of 20% of PCPs were applying combination therapy despite the fact that several studies have indicated that combination therapy is no more effective than an α 1 -adrenoceptor antagonist alone [12, 13, 14]. This is however due to the fact that the survey took place in 1995 before the results of the combination trials were available.…”
Section: Resultsmentioning
confidence: 99%
“…In the nationwide survey, most of the PCPs also mainly prescribed α 1 -adrenoceptor antagonists whereas finasteride was used more rarely [10]. A total of 20% of PCPs were applying combination therapy despite the fact that several studies have indicated that combination therapy is no more effective than an α 1 -adrenoceptor antagonist alone [12, 13, 14]. This is however due to the fact that the survey took place in 1995 before the results of the combination trials were available.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is an option in patients with more severe symptoms who are unable or unwilling to undergo surgery and in those awaiting surgery [118]. However, the onset of action is slow and results from three direct comparative trials of up to 12 months duration showed that finasteride monotherapy was not superior to placebo and clearly less effective compared to α 1 -blocker monotherapy or combination therapy in reducing symptom scores and improving maximum urinary flow rates [119, 120, 121], irrespective of prostate size [119]. …”
Section: An Ebm-look At the Therapeutic Options For Bphmentioning
confidence: 99%
“…In contrast to finasteride [70], there is no limitation to efficacy depending on prostate size [71](as confirmed by uncontrolled observations [72]); additionally, efficacy does not relate to baseline PSA [34]. Recently, magnetic resonance imaging (MRI) estimating the area density of smooth muscle cells in the prostate was shown to help to predict Q max -responsiveness to α 1 -blockade [73].…”
Section: Rcts With α1-blockers For Lutsmentioning
confidence: 99%